Social determinants of health and COVID-19: An evaluation of racial and ethnic disparities in attitudes, practices, and mental health - Jenil R. Patel; Clare C. Brown; T. Elaine Prewitt; Zain Alfanek; M. Kathryn Stewart (Public Library of Science (PLoS), 2023)
Previous evaluations have reported racial minorities feel they are at greater risk of contracting COVID-19, but that on average, they have better preventative practices, such as wearing face masks and avoiding large gatherings. In this study, we explored associations between social determinants of health (SDOH), race and ethnicity, COVID-19 practices and attitudes, and mental health outcomes during the pandemic. We examined associations between SDOHs and practices, attitudes, and mental health symptoms by race and ethnicity using multivariable linear and logistic regressions in 8582 Arkansan pulse poll respondents (September-December, 2020). Compared to White respondents, mean attitude and practice scores were greater (indicating safer) among Black (4.90 vs. 3.45 for attitudes; 2.63 vs. 2.41 for practices) and Hispanic respondents (4.26 vs. 3.45 for attitudes; 2.50 vs. 2.41 for practices). Respondents' SDOH scores by race/ethnicity were: White (3.65), Black (3.33), and Hispanic (3.22). Overall, attitude and practice scores decreased by 0.35 and 0.09, respectively, for every one-point increase in SDOH. Overall, a one-point increase in SDOH was associated with 76% and 85% increased odds of screening negative for anxiety and depression, respectively. To conclude, underlying social inequities are likely driving safer attitudes, practices, and worse anxiety and depression symptoms in Black and Hispanic Arkansans. In terms of policy implications, our study supports the urgency of addressing SDOHs for rural states similar to Arkansas.